NEW ECCLESIAL MOVEMENTS - Kochuthara, Shaji George (Asian Horizons, 2010)
Post-modern, post-religious, post-Christian, post-moral, secular, neoliberal, relativist, anarchist, valueless, value-indifferent, consumerist… These are some of the words used to describe the society in which we live today. Many have claimed that the ‘Christian’ West cannot be and will not be any more called Christian and that all over the world, Christianity, and religion in general have become outdated, superfluous and irrelevant. The sharp decline in the past few decades in the number of people regularly attending the Church or those seeking sacramental ministry or the steady growth in the number of those who officially leave the Church may seem to confirm those claims.